Decreased choroidal thickness in eyes with secondary angle closure glaucoma. An aetiological factor for deep retinal changes in glaucoma?. Issue 7 (July 1993) - Kubota, T.; Jonas, J. B.; Naumann, G. O.
Abstract : A decreased count of retinal photoreceptors all over the fundus and a loss of retinal pigment epithelium cells mainly in the parapapillary region have been reported to be associated with glaucoma. This study addressed the question whether this cell loss in the deep retinal layers may be connected with a change of the choroidal thickness in glaucomatous eyes. Histological sections of 12 eyes with secondary angle closure glaucoma due to a malignant melanoma of the ciliary body and 20 eyes with a malignant choroidal melanoma and normal intraocular pressure were histomorphometrically evaluated. Before enucleation the intraocular pressure was significantly higher in the glaucoma group compared with the control group. Thickness of the choroid was measured at 12 locations from the posterior pole to the fundus periphery. The choroid was significantly thinner in the glaucoma group than in the control group. The decreased choroidal thickness was mainly due to a diminished choroidal vessel diameter. The differences were more marked at the optic disc border than in the fundus periphery. The decreased choroidal thickness in the glaucomatous eyes suggests a reduced choroidal perfusion. It fits with the reported lack of autoregulation of the choroidal blood circulation. Considering the diminished choroidal thickness especially in the parapapillary region, it may be one among other factors explaining the changes of the deep retinal layers in eyes with glaucoma. It indicates that thinning of the choroid, besides the chorioretinal atrophy in the parapapillary region, should be added to the panoply of histological changes in glaucoma.